High expression of C-X-C chemokine receptor 4 and Notch1 is predictive of lymphovascular invasion and poor prognosis in lung adenocarcinoma - Zhuangzhuang Cong; Haiwei Wu; Zhong Guo; Tao Qin; Yang Xu; Hua Jing; Yanqing Wang; Yi Shen (Tumor Biology)
C-X-C chemokine receptor 4 and Notch1 have been shown to play oncogenic role individually. This study aimed to determine the combinatorial role of C-X-C chemokine receptor 4 and Notch1 in lung adenocarcinoma. Expression of C-X-C chemokine receptor 4 and Notch1 was detected in resected tumor samples from 185 patients with lung adenocarcinoma at stage I–IIIa by immunohistochemistry. Correlations of their immunoscores with clinicopathological characteristics and disease-specific survival were retrospectively investigated. A three-dimensional capillary-like sprouting model was established to assess the effects of C-X-C chemokine receptor 4 and Notch1 on angiogenesis in vitro. The results revealed that expression of C-X-C chemokine receptor 4 and Notch1 was elevated in lung adenocarcinoma tissues. The high co-expression of C-X-C chemokine receptor 4 and Notch1 was significantly correlated with tumor size, tumor status, nodal status, tumor stage, and lymphovascular invasion, as well as decreased disease-specific survival. Multivariate analysis showed that lymphovascular invasion (hazard ratio: 0.205, 95% confidence interval: 0.086–0.491, p < 0.0001) and co-expression of C-X-C chemokine receptor 4 and Notch1 (hazard ratio: 0.293, 95% confidence interval: 0.168–0.510, p < 0.0001) were independent indicators of poor prognosis in lung adenocarcinoma. Furthermore, Notch1 enhanced the effects of C-X-C chemokine receptor 4 to promote angiogenesis by regulating Flt1 and Flt4 in vitro. In conclusion, co-expression of C-X-C chemokine receptor 4 and Notch1 is associated with tumor progression and lymphovascular invasion and is an independent indicator of poor survival in lung adenocarcinoma. In lung adenocarcinoma patients with high C-X-C chemokine receptor 4 and Notch1 expression, simultaneous inhibition of both factors might be an effective treatment strategy.